Innovation Drivers, Value Chains and the Geography of Multinational Firms in European Regions - Riccardo Crescenzi; Carlo Pietrobelli; Roberta Rabellotti (London School of Economics and Political Science (LSE), European Institute, 2012)
This paper investigates the geography of multinational corporations' investments in the EU regions. The 'traditional' sources of location advantages (i.e. agglomeration economies, market access and labour market conditions) are considered together with innovation and socio-institutional drivers of investments, captured by means of regional "social filter" conditions. The introduction of a wider set of attraction factors makes is possible to empirically assess the different role played by such advantages in the location decision of investments at different stages of the value chain and disentangle the differential role of national vs. local and regional factors. The empirical analysis covers the EU-25 regions and suggests that regional-socio economic conditions are crucially important for an understanding of the location investment decisions in the most sophisticated knowledge-intensive stages of the value chain.
Keywords: F21; F23; O33; R12; R58; 330; Innovation; Multinationals; Systems of Innovation; Value Chains; Regions; European Union